From the Paraguay of the Centenary to Classical Antiquity. Overlap of Temporalities in Eloy Fariña Núñez’s Canto secular (1911) - Villalba Rojas, Rodrigo Nicolás (2022)
In 1911, Eloy Fariña Núñez published in Buenos Aires the long poem Canto secular to commemorate the centenary of Paraguay’s independence. The work displays a modernist stamp, but it also involves some features of Arielism, a Latin American political philosophy that brought youth to the fore and recognized a double American and Greco-Latin cultural ancestry. This article proposes an intertextual and interdiscursive approach to Canto secular, in order to discover in the poem a literary operation of foundation of an enunciative locus where two spatiotemporal coordinates, both literary recreated, overlap: the peasant Paraguay in the transition towards urbanity, and classical antiquity synthesized in some legal values and models.